WORDS AND THEIR HISTORIES: INSIGHTS FROM APPLIED LINGUISTICS (Modern education and development, 2024)
This article examines the historical relevance of terms in applied linguistics, including their etymology, semantic evolution, and social impact. Linguists discover how languages develop throughout time by tracing word histories, which provides significant insights for education, translation, and cross-cultural communication. Real-world examples demonstrate these processes and their importance in applied linguistics.